Antifungal and Antiochratoxigenic Activities of Essential Oils and Total Phenolic Extracts: A Comparative Study - Rachelle EL Khoury; Ali Atoui; Florence Mathieu; Hiba Kawtharani; Anthony EL Khoury; Richard G. Maroun; Andre EL Khoury (MDPI AG, 2017)
This study is intended to prevent ochratoxin A (OTA) production by Aspergillus carbonarius S402 using essential oils (EOs) and total phenolic compounds extracted from plants and herbs. The EOs used in this study are the following: bay leaves, cumin, fenugreek, melissa, mint, and sage. As for the phenolic compounds, they were extracted from bay leaves, cumin, fenugreek, melissa, mint, sage, anise, chamomile, fennel, rosemary, and thyme. The experiments were conducted on Synthetic Grape Medium (SGM) medium at 28 °C for 4 days. OTA was extracted from the medium with methanol and quantified using HPLC (High Performance Liquid Chromatography). Results showed that EOs had a greater impact than the total phenolic extracts on the OTA production. Reduction levels ranged between 25% (sage) and 80% (melissa) for the EOs at 5 µL mL−1, and 13% (thyme) and 69% (mint) for the phenolic extracts. Although they did not affect the growth of A. carbonarius, total phenolic extracts and EOs were capable of partially reducing OTA production. Reduction levels depended on the nature of the plants and the concentration of the EOs. Reducing OTA with natural extracts could be a solution to prevent OTA production without altering the fungal growth, thus preserving the natural microbial balance.